Gas Geyser a Silent Killer in Bathroom: A Case Report of Carbon Monoxide Poisoning - Kumar, Yogesh; Paliwal , P K; Sirohiwal, B L; Khanagwal, Vijay Pal; Sharma , Luv (Journal of Indian Academy of Forensic Medicine, 2014)
In the ever changing world with increasing population and limited resources, development of alternate sources to restricted energy assets, which though have made life easier, also has its side effects which may vary from minor consequences to fatality. Heating appliances especially gas geysers, though an efficient means of energy conservation especially during the winter months are no exception to it. Here, we present the case of a 32 year old female with fatal carbon monoxide poisoning from a running gas geyser. The victim had no history of chronic diseases or any other ailment and was in fair health. She was found dead in her bathroom floor. The subsequent autopsy findings, crime scene examination and investigation confirmed the cause and manner of death to be accidental carbon-monoxide poisoning. This case will bring into light, the ongoing trend of using gas geysers instead of traditional electric geysers mainly based on cost effectiveness which has in turn led to an alarming rise in such accidents. We will also suggest the routine precautions which can be followed to prevent such tragic accidents.